The influence of the retro trend on the pattern and symbol of ceramic decoration in the Qianlong period of the Qing Dynasty / Li Ying and Wan Jamarul Imran Wan Abdullah Thani - Li, Ying; Wan Abdullah Thani, Wan Jamarul Imran (Faculty of Art and Design, 2023)
China's ceramic production has a long history. At the peak of the development of Chinese ceramic art, the Qianlong period of the Qing Dynasty left many precious ceramic artworks. Many exquisite ceramic decorations, some of which have clear historical retro elements, were left. This paper uses the methods of formal analysis and iconography to study the retro ceramic decorative patterns in the Qianlong period of the Qing Dynasty and analyzes the influence of the retro trend on the pattern and symbolic connotation of decorative patterns. What artistic style do these decorative patterns have, and what are the hidden social driving factors behind them.